Cancer epidemiology and trends in Sistan and Baluchestan province, Iran - Rafiemanesh, Hosein (Med J Islam Repub Iran, 2015)
Background: Cancer is the second leading cause of death in developing countries. In Iran, cancer is the third cause of death. The present study aimed at providing the incidence rates (crude and agestandardized) of different types of cancers in Sistan and Baluchestan province (Southeastern of Iran). Methods: Data were collected retrospectively reviewing all new cancer patients registered in Cancer Registry Center of Health Heputy for Sistan and Baluchestan province. Common cancers were defined based on the number of cases and standardized incidence rates. To compute the annual percentage change (APC), joinpoint 4.1.1.1 software was applied. Results: A total of 3535 cases of cancers registered during 2004-2009 were identified. Of these, 46.82% occurred in females and 53.18% in males. The most frequent cancer in women was breast cancer followed by esophagus, skin, colorectal and leukemia. The 5 most frequent cancers in men were stomach, skin, leukemia, esophagus and bladder. Joinpoint analyze showed a significant increasing trend for adjusted standard incidence rate (ASIR) for both sexes (p<0.05). Conclusion: According to The results of the present study and comparison to previous studies for other provinces in Iran, cancer incidence in Sistan and Baluchistan is less common but trends of cancers are increasing in Sistan and Baluchestan Province. It is necessary to have a comprehensive health policy for prevention and control of this problem.